Key factors for ensuring performance and attracting practitioners to small sport clubs. (20th December 2019) - Musso, Fabio; Richelieu, André; Francioni, Barbara
The main objective of this paper is to determine which factors small and non-profit sports clubs should consider and implement in order to, first, enhance performance and, second, attract practitioners. To achieve our objective, we carried out a regression analysis on a sample of clay target shooting clubs. Results reveal that factors related to shooting practice, as well as facilities/services supporting practitioners have a positive influence on performance. Moreover, well-defined animation and stimulus policies for members emerged as factors with a positive impact on performance. This study provides an analysis of the connection between infrastructure and organisational features of sports clubs, on the one hand, and performance, on the other. This research also points out which types of services and initiatives should be adopted for enhancing both clubs' attractiveness and performance.